An impaired glucagon-like peptide-1 response is associated with prediabetes in polycystic ovary syndrome with obesity. Issue 10 (October 2019) - Ferjan, Simona; Jensterle, Mojca; Oblak, Tjasa; Zitnik, Irena Prodan; Marc, Janja; Goricar, Katja; Dolzan, Vita; Janez, Andrej
Objective: Impaired glucose homeostasis in polycystic ovary syndrome (PCOS) is associated with obesity, age, and disease phenotype. This study aimed to investigate the glucagon-like peptide-1 (GLP-1) response in patients with obesity and PCOS with normal glucose tolerance (NGT) or prediabetes. Methods: Twenty-six women with obesity and PCOS were included. Thirteen women had NGT and 13 had prediabetes. Serum glucose, insulin, and GLP-1 levels were measured during an oral glucose tolerance test. Beta-cell function and insulin resistance were determined. Results: Women with prediabetes had significantly lower GLP-1 levels than did those with NGT after a glucose load. GLP-1 levels <3.02 pM at 120 minutes were associated with prediabetes. Women with prediabetes had a lower oral glucose insulin sensitivity (OGIS) index and greater amount of visceral adipose tissue than did those with NGT. Plasma GLP-1 levels at 120 minutes were correlated with visceral adiposity and the OGIS index. A change in GLP-1 levels was correlated with a family history of type 2 diabetes. Conclusion: The GLP-1 response is lower in patients with obesity, PCOS, and prediabetes than in those with obesity, PCOS, and NGT. Further investigation of the GLP-1 response as a potential separate risk factor for prediabetes in PCOS is required.